PENERAPAN TOTAL QUALITY MANAGEMENT PADA PROGRAM STUDI MPI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN - Syahid Syahid (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
The purpose of this paper is to describe (1) the concept of total quality mana-gement, (2) the theoretical foundation of total quality management, and (3) the application of total quality management in Education management study program at the Faculty of Education and Teaching Science, UIN Alauddin Ma-kassar. There are some theoretical bases to support the implementation of TQM in educational institutions. One is the theory of Deming which can be identified from (a) Deming’s chain reaction model, (b) Deming’s continuous improvement cycle, (c) Deming’s theory of Variance, and (d) Deming's fourteen points of management. The application of TQM in Management Studies Program Faculty of Tarbiyah and Teaching Education UIN Alauddin have not maximized. The data indicated that 70.19% respondents said that the implementation of TQM is at a mediocre level, 0.90% respondents said good, and 1.85% respondents said that the implementation of TQM has been very good.